Novel long-chain neurotoxins from Bungarus candidus distinguish the two binding sites in muscle-type nicotinic acetylcholine receptors. Issue 8 (26th April 2019) - Utkin, Yuri N.; Kuch, Ulrich; Kasheverov, Igor E.; Lebedev, Dmitry S.; Cederlund, Ella; Molles, Brian E.; Polyak, Iakov; Ivanov, Igor A.; Prokopev, Nikita A.; Ziganshin, Rustam H.; Jornvall, Hans; Alvelius, Gunvor; et al.
Abstract : αδ-Bungarotoxins, a novel group of long-chain α-neurotoxins, manifest different affinity to two agonist/competitive antagonist binding sites of muscle-type nicotinic acetylcholine receptors (nAChRs), being more active at the interface of α–δ subunits. Three isoforms (αδ-BgTx-1–3) were identified in Malayan Krait ( Bungarus candidus ) from Thailand by genomic DNA analysis; two of them (αδ-BgTx-1 and 2) were isolated from its venom. The toxins comprise 73 amino acid residues and 5 disulfide bridges, being homologous to α-bungarotoxin (α-BgTx), a classical blocker of muscle-type and neuronal α7, α8, and α9α10 nAChRs. The toxicity of αδ-BgTx-1 (LD50  = 0.17–0.28 µg/g mouse, i.p. injection) is essentially as high as that of α-BgTx. In the chick biventer cervicis nerve–muscle preparation, αδ-BgTx-1 completely abolished acetylcholine response, but in contrast with the block by α-BgTx, acetylcholine response was fully reversible by washing. αδ-BgTxs, similar to α-BgTx, bind with high affinity to α7 and muscle-type nAChRs. However, the major difference of αδ-BgTxs from α-BgTx and other naturally occurring α-neurotoxins is that αδ-BgTxs discriminate the two binding sites in the Torpedo californica and mouse muscle nAChRs showing up to two orders of magnitude higher affinity for the α–δ site as compared with α–ε or α–γ binding site interfaces. Molecular modeling and analysis of the literature provided possible explanations for these differences in binding mode; one of the probable reasons being the lower content of positively charged residues in αδ-BgTxs. Thus, αδ-BgTxs are new tools for studies on nAChRs.